Review article on utilization and perception of health services under Janani Suraksha Yojna among mothers - Eram, Uzma (International Journal Of Community Medicine And Public Health, 2017)
Janani Suraksha Yojana (JSY) is the name in Hindi language that literally means “maternal protection scheme. Janani Suraksha Yojana (JSY) is a safe motherhood intervention under the National Health Mission (NHM). Earlier it was known as National Rural Health Mission (NRHM) it is being implemented with the objective of reducing maternal and neonatal mortality by promoting institutional delivery among poor pregnant women. The scheme is under implementation in all states and union territories, with a special focus on low performing states. The scheme seeks to reduce maternal and neo-natal mortality by promoting institutional delivery, that is, by providing a cash incentive to mothers who deliver their babies in a health facility. There is also provision for incentives to Accredited Social Health Activists (ASHA) for encouraging mothers to go for institutional delivery. The scheme is fully sponsored by the Central Government and is implemented in all states and Union Territories, with special focus on low performing states like Uttar Pradesh.